Demographic factors that influence performance on the Praxis Earth and Space Science: Content Knowledge Test. Issue 4 (2nd October 2021) - Ndembera, Rachel; Hao, Jie; Fallin, Rebekah; Ray, Herman E.; Shah, Lisa; Rushton, Gregory T.
Abstract: What teachers know about their content area plays a role in how they effectively enhance the scientific literacy of their students. This leads to questions about teacher content knowledge as they enter the field. The Praxis Earth and Space Science: Content Knowledge Test is the most widely used licensure assessment for aspiring Earth science teachers in the United States. There are few previous reports on the personal and professional characteristics of those test-takers which would provide information about Earth science teacher candidates. This study presents findings based on analysis of trends in reported demographic variables and scaled scores for examinees assessed by the licensure exam from June 2006 to May 2016 in order to identify which have the highest correlation with their performance. Three major themes emerged as a result of the study: there is currently a large proportion of out of field teaching, a lack of diversity among test-takers, and underperformance of Black/African American test-takers when compared to their White counterparts as well as in females compared to males. Our analysis uncovered more subtle differences in performance based on undergraduate GPA and age group as well. Findings from this study suggest recommendations for improving focused recruitment and retention efforts to support identified at-risk populations enrolled in Earth science teacher preparation programs.